FACTORS INFLUENCING EMPLOYEE PRODUCTIVITY IN FACTORIES IN ROYAL GROUP PHNOM PENH SPECIAL ECONOMIC ZONE - Sun, Samoeun; Try, Sothearith; Long, Sovang (Srawung: Journal of Social Sciences and Humanities, 2025)
Employee productivity plays a critical role in determining organizational success, influencing profitability, efficiency, and global competitiveness. This research investigates the determinants of employee productivity in factories within the Royal Group Phnom Penh Special Economic Zone (RGPPSEZ), focusing on welfare facilities, wages and benefits, working conditions, training and development, and employee motivation across 20 factories. A quantitative research design involved gathering data from 600 workers through structured questionnaires. The data was analyzed using Confirmatory Factor Analysis (CFA) and Structural Equation Modelling (SEM) to examine the relationships between independent variables: welfare facilities, wages and benefits, working conditions, training and development, and employee motivation and the dependent variable: employee productivity. The findings indicated that welfare facilities and training and development significantly impacted employee motivation, which in turn positively affected productivity. Interestingly, wages and benefits and working conditions showed no significant impact on motivation while the relationship between training and development and employee productivity was deemed insignificant. These insights highlight the importance of prioritizing welfare facilities and robust training programs to enhance employee motivation and productivity within the RGPPSEZ context.